2020
DOI: 10.1002/mrm.28537
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical study of diffusion‐weighted MRI contrast as an early indicator of thermal ablation

Abstract: Intraoperative T 2-weighted (T2-w) imaging unreliably captures image contrast specific to thermal ablation after transcranial MR-guided focused ultrasound surgery, impeding dynamic imaging feedback. Using a porcine thalamotomy model, we test the unproven hypothesis that intraoperative DWI can improve dynamic feedback by detecting lesioning within 30 minutes of transcranial MR-guided focused ultrasound surgery. Methods: Twenty-five thermal lesions were formed in six porcine models using a clinical transcranial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…reported a decrease in tissue ADC following ablation in the prostate[48][49][50], uterine fibroids[8,9,47,51], and brain[52][53][54]. The treated lesion size, as measured on diffusion MRI, has been found to correlate well with contrastenhanced T1w images (Figure1(e)) and histopathology.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…reported a decrease in tissue ADC following ablation in the prostate[48][49][50], uterine fibroids[8,9,47,51], and brain[52][53][54]. The treated lesion size, as measured on diffusion MRI, has been found to correlate well with contrastenhanced T1w images (Figure1(e)) and histopathology.…”
mentioning
confidence: 83%
“…These competing effects can make diffusion-based contrast difficult to interpret [ 47 ]. However, several studies have reported a decrease in tissue ADC following ablation in the prostate [ 48 50 ], uterine fibroids [ 8 , 9 , 47 , 51 ], and brain [ 52 54 ]. The treated lesion size, as measured on diffusion MRI, has been found to correlate well with contrast-enhanced T1w images ( Figure 1(e) ) and histopathology.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Immediately after the insonation, each subject was removed from the Insightec system and placed prone in an 8-channel imaging coil. MRI images (T1 and T2-weighted SPACE, 3D-MPRAGE, Diffusion-weighted MRI) were then acquired; diffusion-weighted sequences were considered particularly significant as an early indicator of post-treatment lesion ( 21 ). Contrast-enhanced T1 scans were not considered due to the lack of a pathological lesion to produce extravasation of Gadolinium, nor the necessity to asses contrast extravasation as for blood brain barrier opening.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, beside investigations of EDBS, as proposed in Chapter 5, image-based indicators should also be investigated. Potential image-based predictors have been proposed in the last few years, but their clinical relevance is yet to be validated [82,83,198,199]. Diffusion-weighted MRI (DWI) contrast has shown promising preliminary results in preclinical and clinical studies [82,198,199].…”
Section: The Role Of Mr For Hifu Procedures On Bone Metastasesmentioning
confidence: 99%
“…Potential image-based predictors have been proposed in the last few years, but their clinical relevance is yet to be validated [82,83,198,199]. Diffusion-weighted MRI (DWI) contrast has shown promising preliminary results in preclinical and clinical studies [82,198,199]. The preclinical studies suggested that DWI can detect lesion formation [198] and changes in the muscle overlying the periosteum [199]caused by ablation, while the clinical study showed correlation between the apparent diffusion coefficient with pain relief [82].…”
Section: The Role Of Mr For Hifu Procedures On Bone Metastasesmentioning
confidence: 99%